Horizontal gene transfers dominate the functional mitochondrial gene space of a holoparasitic plant - Garcia, Laura Evangelina (2021)
Although horizontal gene transfer (HGT) is common in angiosperm mitochondrial DNAs (mtDNAs), few cases of functional foreign genes have been identified. The one outstanding candidate for large-scale functional HGT is the holoparasite Lophophytum mirabile, whose mtDNA has lost most native genes but contains intact foreign homologs acquired from legume host plants. To investigate the extent to which this situation results from functional replacement of native by foreign genes, functional mitochondrial gene transfer to the nucleus, and/or loss of mitochondrial biochemical function in the context of extreme parasitism, we examined the Lophophytum mitochondrial and nuclear transcriptomes by deep paired-end RNA sequencing. Most foreign mitochondrial genes in Lophophytum are highly transcribed, accurately spliced, and efficiently RNA edited. By contrast, we found no evidence for functional gene transfer to the nucleus or loss of mitochondrial functions in Lophophytum. Many functional replacements occurred via the physical replacement of native genes by foreign genes. Some of these events probably occurred as the final act of HGT itself. Lophophytum mtDNA has experienced an unprecedented level of functional replacement of native genes by foreign copies. This raises important questions concerning population-genetic and molecular regimes that underlie such a high level of foreign gene takeover.